A Research Note on Bargain Purchase Gains on Acquisition. Issue 2 (23rd September 2018) - Kabir, Humayun
Abstract: This research note explores the incidence, amounts, disclosure and potential sources of bargain purchase gains reported by an Australian sample of firms during 2013–15. It finds that 7.58% of the sample acquirers reported bargain purchase gains during this period. The median gain as a percentage of consideration transferred was 18.90%. In contravention of IFRS 3 Business Combinations, not all acquirers with material bargain purchase gains disclosed in notes why the gain arose. Finally, the note reports preliminary evidence suggesting uncertainty about the sources of the gain. Abstract : This research note explores the incidence, amounts, disclosure and potential sources of bargain purchase gains on acquisitions in Australia from 2013–15.